The book of everlasting things eaudiobook A novel. - Malhotra, Aanchal (Macmillan Audio, 2022)
FOR FANS OF ALL THE LIGHT WE CANNOT SEE , A LUSH, SWEEPING LOVE STORY ABOUT A HINDU PERFUMER AND A MUSLIM CALLIGRAPHER, SET AGAINST THE BACKDROP OF PARTITION "Narrator Deepti Gupta captures the deep emotional connection between the two young people, making listeners feel hopeful that, in some way, Samir and Firdaus will find a way to be together. As listeners follow the pair through the decades and see the long-term effects of the partition, Gupta's performance complements this sweeping story, dazzling with every new chapter and plot twist." - AudioFile Magazine (Earphones Award Winner) "The excellent audio production uses Indian music to open and close the epic, and narrator Deepti Gupta speaks with a lovely Indian accent that listeners will acclimate to easily." - Library Journal On a January morning in 1938, Samir Vij first locks eyes with Firdaus Khan through the rows of perfume bottles in his family's ittar shop in Lahore. Over the years that follow, the perfumer's apprentice and calligrapher's apprentice fall in love with their ancient crafts and with each other, dreaming of the life they will one day share. But as the struggle for Indian independence gathers force, their beloved city is ravaged by Partition. Suddenly, they find themselves on opposite sides: Samir, a Hindu, becomes Indian and Firdaus, a Muslim, becomes Pakistani, their love now forbidden. Severed from one another, Samir and Firdaus make a series of fateful decisions that will change the course of their lives forever. As their paths spiral away from each other, they must each decide how much of the past they are willing to let go, and what it will cost them. Lush, sensuous, and deeply romantic, The Book of Everlasting Things is the story of two lovers and two nations, split apart by forces beyond their control, yet bound by love and memory. Filled with exquisite descriptions of perfume and calligraphy, spanning continents and generations, Aanchal Malhotra's debut novel is a feast for the senses and the heart. A Macmillan Audio production from Flatiron Books.